Roux-en-Y gastric bypass in the elderly: is age a determining factor in our outcomes? - Turchi, Matías J; Kingma, Feike; Laborda, Nicolás; Montanelli, Agostina; Maldonado, Juan M; Fiolo, Felipe E (Elsevier, 2020)
BACKGROUND: While patients are becoming older and the prevalence of obesity increases worldwide, literature on the impact of age on outcomes after laparoscopic Roux-en-Y gastric bypass (LRYGB) is scarce. The balance between surgical risks and clinical benefits of LRYGB are unclear in relation to age. OBJECTIVES: To evaluate the impact of age on the risk of postoperative complications, postoperative weight loss, and remission of co-morbidities for patients who underwent LRYGB. SETTING: A high-volume center for bariatric surgery. METHODS: A retrospective analysis of 582 patients who underwent LRYGB was performed. Linear logistic regression analyses were performed to evaluate the potential impact of age on the postoperative percentage of total weight loss (%TWL). Multivariable binary logistic regression analyses were performed to evaluate whether age was independently associated with the risk of postoperative complications and likelihood of remission of co-morbidities (hypertension, diabetes, and dyslipidemia). In addition, these outcomes were descriptively analyzed for the following 3 age groups: the young (18-39 yr), the middle aged (40-59 yr), and the elderly (≥60 yr). RESULTS: Patients with hypertension were more prone to developing postoperative complications (odds ratio 2.435, 95% confidence interval: 1.241-4.777) and no other factors were found to be associated with the risk of postoperative complications. Older age was significantly associated with lower %TWL at a postoperative follow-up of 6 (ß = -.117, P = .004), 12 (ß = -.177, P < .001), and 36 months (ß = -.169, P = .001), but not at 60 months (ß = -.097, P = .161). Nonetheless, a %TWL of 30% was observed in patients who were >60 years at the time of surgery. Age was not associated with the likelihood of co-morbidity resolution after LRYGB. The remission of hypertension was less likely in patients with co-existence of diabetes (odds ratio .334, 95% confidence interval: .136-.821) and in patients with a longer length of postoperative follow-up (odds ratio .982, 95% confidence interval: .966-.998). CONCLUSIONS: Although older age seems to be associated with lower postoperative %TWL, elderly patients can still achieve a %TWL of 30% after LRYGB. In this study, age was not found to be an independent predictor of postoperative complications nor the likelihood of co-morbidity resolution. Therefore, older age alone should not be an absolute contraindication for LRYGB.
Keywords: Bariatric surgery; Elderly patients; Gastric bypass; Obesity; Remission; Weight loss; Taverne; Surgery; Journal Article